Strata Treemaps - Choi, Junghong; hyun Kwon, Oh; Lee, Kyungwon (SIGGRAPH'11: Posters of the Special Interest Group on Computer Graphics and Interactive Techniques Conference, 2011)
Treemap is a method of visualization to recognize a hierarchical structure of data using the size and arrangement of nested rectangles. A limitation of a treemap is the difficulty to discern the structure of a hierarchy. Several approaches have been proposed to improve the visibility of the hierarchical structure. These approaches involve the use of a border or padding to emphasize the hierarchical structure. However, this leads to a disparity between the node weight and the relative node size.